Towards sustainable development by new town planning. Case study of Mazandaran Province of Iran. - Zahedi, Ali (My University, 2019)
Das New-Town-Planungskonzept wurde als alternative Lösung zur Regulierung des Stadt-Land-Wachstums in der iranischen Provinz Mazandaran evaluiert. Die Evaluation wurde unter drei Gesichtspunkten durchgeführt. (1) lokale Entwicklung durch die Gründung von Kleinunternehmen mit Low-Tech-Lösungen. (2) Beurteilung des Wohlbefindens im Dorf Kandelous anhand der Kriterien Wohnen, Einkommen und Arbeit, Work-Life-Balance, Bildung, Umweltqualität, Gesundheit, bürgerschaftliches Engagement und Governance, persönliche Sicherheit, soziale Zusammenhänge, Glück und Themen der Lebenszufriedenheit. Abschließend wurde die Region mit einer integrierten GIS-AHP-Technik hinsichtlich einer Eignung für New Town-Siedlungen untersucht.

The New Town planning concept was evaluated as an alternative solution for regulating imbalanced urban-rural growth in the Mazandaran province of Iran. The research was conducted in three main aspects. Firstly, local development through creation of small-scale enterprises with low-tech solutions was studied by analysing several small-scale businesses. Secondly, human well-being assessment was conducted in the Kandelous village by considering housing, earning and job, work-life balance, education, environmental quality, health, civic engagement and governance, personal security, social connections, happiness, and life satisfaction topics. Thirdly, the study area was assessed to identify suitable place for creating New Town settlement by using an integrated GIS-AHP technique that was followed by a validation step using high resolution Google Earth images and a field study survey.
Keywords: Nachhaltige Stadtentwicklung; Ländlicher Raum; Stadt-Land-Problem; Bevölkerungsansiedlung; Stadtneugründung; Querschnittsanalyse; Sozialökonomie; Dorfgemeinschaft; Planungskonzept; Eignung; Analyse(geografisch); Low-Technology; Stadtplanung; Sozialökologie; New Town; Sozialökologie